BİR YENİDEN YAPILANMA KURAMIMIZ VAR MI?- Yenilenmeci İdeolojinin Sorunları ve Geleceği Üzerine- - Mehmet Evkuran (İslami İlimler Dergisi)
Renaissance is a problem of mentality and it requires mental evolution radically. In Islamic tradition innovation and tajdeet has begun discussed as a fundamental problem dedicatedly in the ends of 19th century. Many thinkers and scholars have written boks and articles on this matter. Nowadays we can understand that the innovation is a subject related with wider and systematic aspect. The scope of innovation has developed and contained these matters: perception of society, tradition, references and sources, definition of belief/iman, ethics, Islamic sciences, modern world.